The Effect of Circular Economy Implementation, Environmental Awareness, and Green Technology on Resource Efficiency in Manufacturing Industries in West Java - Judijanto, Loso; Haryanto, Anung; Setiyawan, Heri (West Science Social and Humanities Studies, 2024)
This study examines the effects of circular economy implementation, environmental awareness, and green technology adoption on resource efficiency in manufacturing industries in West Java. Using quantitative analysis, data were collected from 190 respondents through a Likert-scale questionnaire (1-5) and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that all three factors significantly enhance resource efficiency, with green technology showing the strongest impact. Circular economy practices optimize resource utilization, while environmental awareness fosters sustainable organizational behavior. The integration of these factors explains 62% of the variance in resource efficiency, highlighting the importance of an integrated approach to sustainability. The study provides actionable insights for policymakers and industry leaders to promote sustainable practices and adopt green innovations in manufacturing.